Structural Model for Preparing Safe and Hygienic Complementary Food in Indonesia - Lucy Widasari; Anto J. Hadi; Haslinah Ahmad; Wirawan Setyalaksana; Lusy Damayanti; Elly Sutrisni (Journal of Public Health and Pharmacy, 2024)
Introduction: Early childhood nutrition is a fundamental determinant of optimal growth and development. The study aimed to evaluate how mothers provide complementary feeding (CF) to infants and young children aged 6–23 months. It explored factors influencing the adoption of safe and hygienic CF practices recommended by the WHO and Infant and Child Feeding Guidelines. Methods: A non-experimental quantitative approach surveyed 1125 mothers across 28 districts/cities. Reliability was assessed using composite reliability (?_c), ensuring reliability threshold (?0.7) was met. Although most constructs comprised single items, they were deemed reliable. Results: Findings indicated that being the first child didn't significantly impact maternal understanding of CF (?=0.034, p=0.215) or adherence to safe CF practices (?=-0.001, p=0.307). Maternal employment status also showed no significant influence on CF knowledge (?=0.022, p=0.492) or safe CF practices (?=-0.01, p=0.568). However, maternal education significantly affected CF knowledge (?=0.060, p<.001) and safe CF practices (?=-0.030, p=0.004). Conclusion: In essence, higher maternal education levels correlated with better understanding of CF, thereby indirectly promoting safe and hygienic CF preparation.